Self-reported chronic pain is associated with physical performance in older people leaving aged care rehabilitation - Pereira LS (Dove Medical Press, 2014)
Leani Souza Máximo Pereira,1,2 Catherine Sherrington,2,3 Manuela L Ferreira,2 Anne Tiedemann,2,3 Paulo H Ferreira,4 Fiona M Blyth,5 Jacqueline CT Close,3,6 Morag Taylor,3,6 Stephen R Lord3 1Department of Physiotherapy, School of Physical Education, Physiotherapy, and Occupational Therapy, Universidade Federal de Minas Gerais, Belo Horizonte, Brazil; 2Musculoskeletal Division, The George Institute for Global Health, The University of Sydney, Sydney, Australia; 3Neuroscience Research Australia, University of New South Wales, Sydney, Australia; 4Discipline of Physiotherapy, Faculty of Health Sciences, The University of Sydney, Sydney, Australia; 5Pain Management and Research Institute, Royal North Shore Hospital, The University of Sydney, Sydney, Australia; 6Prince of Wales Clinical School, University of New South Wales, Sydney, Australia Background/objectives: The impact of pain on the physical performance of patients in aged care rehabilitation is not known. The study sought to assess 1) the prevalence of pain in older people being discharged from inpatient rehabilitation; 2) the association between self-reported pain and physical performance in people being discharged from inpatient rehabilitation; and 3) the association between self-reported pain and physical performance in this population, after adjusting for potential confounding factors. Methods: This was an observational cross-sectional study of 420 older people at two inpatient aged care rehabilitation units. Physical performance was assessed using the Lower Limb Summary Performance Score. Pain was assessed with questions about the extent to which participants were troubled by pain, the duration of symptoms, and the impact of chronic pain on everyday activity. Depression and the number of comorbidities were assessed by questionnaire and medical file audit. Cognition was assessed with the Mini-Mental State Examination. Results: Thirty percent of participants reported chronic pain (pain lasting more than 3 months), and 17% reported that this pain interfered with daily activities to a moderate or greater extent. Chronic pain (P=0.013) and chronic pain affecting daily activities (P<0.001) were associated with a poorer Lower Limb Summary Performance Score. The relationship between chronic pain affecting daily activities and Lower Limb Summary Performance Score remained significant (P=0.001) after adjusting for depression, age, comorbidities, and Mini-Mental State Examination score. This model explained 10% of the variability in physical performance. Conclusion: One-third of participants reported chronic pain, and close to one-fifth reported that this pain interfered with daily activities. Chronic pain was associated with impaired physical performance, and this relationship persisted after adjusting for likely confounding factors. Keywords: pain, older people, physical performance, rehabilitation